Concizumab in patients with Hemophilia A/B: a systematic review - Valle-Chafloque, Ana (2022)
Objective: We systematically assessed the efficacy of Concizumab in patients with Hemophilia A/B. Material and Methods: Five databases were searched up to May 2022 for randomized controlled trials in adults with severe Hemophilia A/B with or without inhibitors treated with Concizumab compared to standard care or placebo. Outcomes were bleeding episodes (ABRs), D - dimer, prothrombin fragment 1.2, fibrinogen levels, prothrombin time, nasopharyngitis, and upper respiratory tract infection. Results: Two RCTs (n = 86) were included. In both studies, decreased bleeding rates were observed at high levels of concizumab. Furthermore, both studies support the use of concizumab as a safe and well-tolerated prophylactic therapy administered subcutaneously in all haemophilia patients. Placebo was the comparator in one RCT, while Eptacog alfa (activated) rFVIIIa was the comparator in the other RCT. The dosing of concizumab in the RCTs ranged from 0.15, 0.20, 0.25, 0.5 and 0.8, mg/kg with follow-up times between 42 days and 24 weeks. Conclusion: The efficacy and safety of Concizumab for the treatment of patients with Hemophilia A/B cannot be estimated or recommended due to the weak evidence and low number of relevant studies supporting its use.